A New RH-Regular Matrix Derived by Jordan’s Function and Its Domains on Some Double Sequence Spaces - Sezer Erdem; Serkan Demiriz (Journal of Function Spaces)
In the present study, we introduce a new RH-regular 4D (4-dimensional) matrix derived by Jordan’s function and define double sequence spaces by using domains of 4D Jordan totient matrix Jt on some classical double sequence spaces. Also, the α-, βϑ-, and γ-duals of these spaces are determined. Finally, some classes of 4D matrices on these spaces are characterized.